Biological Control Stem Rot Diseases (Sclerotium Rolfsii) on Peanut (Arachis hypogaea L.) using Arbuscular Mycorrhizal Fungi (AMF) Indigenous - Swandi, Fradilla; Sulyanti, Eri; Darnetty, Darnetty (Akta Agrosia, 2021)
Arbuscular Mycorrhizal Fungi (AMF) are known to have potential as biological agents controlling plant pathogens. This study aims to obtain indigenous AMF isolates that can suppress the attack of Sclerotium rolfsii which causes stem rot disease in peanut. The method used is an experimental method with a Completely Randomized Design with 5 treatments, namely A : AMF Glomus sp-3 + S. rolfsii; B: AMF Acaulospora sp + S. rolfsii; C: AMF Gigaspora sp + S. rolfsii; D: Combined AMF Glomus sp-3, Acaulospora sp, and Gigaspora sp + S. rolfsii; E: Without AMF + S. rolfsii (Control). Each treatment was repeated 5 times. The data were analyzed using Analysis of Variance (ANOVA) using the Statistix 8 program and the Least Significance Different (LSD) test at a 5% significance level. The results showed that the isolates of Acaulospora sp and Gigaspora sp were able to increase the resistance of peanut plants to stem rot disease (suppressing the incidence and severity of the disease) reaching 100%. Keywords: Arbuscular Mycorrhizal Fungi, indigenous, salicylic acid, Sclerotium rolfsii.